A garantia dos direitos das pessoas transgênero no SUS: uma análise do Processo Transexualizador - Oliveira, Luísa Zini de (My University, 2026)
This undergraduate thesis examines the limits and possibilities of guaranteeing the rights of transgender people within the scope of the Transsexualization Process in the Brazilian Unified Health System (SUS). It is guided by the following research question: How do the regulations that structure the Transgender Process guide the guarantee of the rights of transgender people within the Brazilian Unified Health System (SUS), and what limitations and possibilities arise in the effective implementation of these rights in contemporary times? The study aims to analyze how these regulations guide the guarantee of transgender rights within SUS, identifying the limits and possibilities involved in the effective realization of these rights in contemporary society. Methodologically, this study is based on bibliographic and documentary research, guided by historical-dialectical materialism and grounded in the categories of totality, historicity, and contradiction. The analysis draws on legislation and ministerial regulations that structure the Transsexualization Process within SUS, as well as on theoretical contributions from gender studies, the right to health, and Social Work. The documentary research was systematized through an analytical matrix designed to identify the rights established in the selected regulations, their implementation mechanisms, their relevance to the transgender population, and the gaps and contradictions present in these normative frameworks. The findings indicate that, despite advances in the institutional recognition of transgender rights within public health, contradictions persist both in the regulatory frameworks governing the Transsexualization Process and in their practical implementation, shaped by macrostructural, institutional, and professional factors. These contradictions are expressed in barriers to access, the persistence of pathologizing perspectives, and inequalities in the organization of health services, materializing in limitations such as the regional concentration of services, the need for users to travel in order to access care, long waiting times, diagnostic requirements for access to care, and the persistence of discriminatory practices in everyday institutional settings. As possibilities for addressing these challenges, the Social Work literature highlights the strengthening of public policies, the technical, ethical, and political qualification of professional teams, and the development of socio-educational actions committed to equity and comprehensive access to healthcare. The study concludes that the Transsexualization Process within SUS constitutes a contradictory space, simultaneously marked by advances in the formal guarantee of rights and by limitations in their effective realization. It also highlights the need for further studies on the implementation of public health policies aimed at the transgender population, as well as for updating the regulatory frameworks governing the Transsexualization Process in light of contemporary debates on depathologization, autonomy, gender identity recognition, and comprehensive care. [resumo fornecido pelo autor]
O presente Trabalho de Conclusão de Curso aborda os limites e as possibilidades da garantia dos direitos das pessoas transgênero no âmbito do Processo Transexualizador no Sistema Único de Saúde (SUS). Parte do seguinte problema de pesquisa: Como as normativas que estruturam o Processo Transexualizador orientam a garantia dos direitos das pessoas transgênero no SUS e quais limites e possibilidades se apresentam na efetivação desses direitos na contemporaneidade? Tem como objetivo analisar como essas normativas orientam a garantia dos direitos das pessoas transgênero no SUS, identificando os limites e as possibilidades presentes na efetivação desses direitos na contemporaneidade. Metodologicamente, trata-se de uma pesquisa bibliográfica e documental, orientada pelo materialismo histórico-dialético e fundamentada nas categorias de totalidade, historicidade e contradição. A análise apoia-se em legislações e portarias que estruturam o Processo Transexualizador no SUS, bem como em produções teóricas dos estudos de gênero, do direito à saúde e do Serviço Social. A pesquisa documental foi sistematizada por meio de uma matriz analítica voltada à identificação dos direitos previstos, dos mecanismos de implementação, da relevância para a população trans e das lacunas e contradições presentes nas normativas selecionadas. Os resultados indicam que, embora tenham ocorrido avanços no reconhecimento institucional dos direitos da população trans no âmbito da saúde pública, persistem contradições tanto nos marcos normativos que estruturam o Processo Transexualizador quanto em sua efetivação concreta, atravessadas por fatores macroestruturais, institucionais e profissionais. Essas contradições expressam-se especialmente nas barreiras de acesso, na permanência de perspectivas patologizantes e nas desigualdades presentes na organização dos serviços de saúde, materializando-se em limites como a concentração regional dos serviços, os deslocamentos dos usuários, os longos tempos de espera, a exigência de critérios diagnósticos para acesso ao cuidado e a persistência de práticas discriminatórias no cotidiano institucional. Como possibilidades de enfrentamento, a literatura do Serviço Social aponta o fortalecimento das políticas públicas, a qualificação técnico-ético-política das equipes e o desenvolvimento de ações socioeducativas comprometidas com a equidade e o acesso integral à saúde. Conclui-se que o Processo Transexualizador no SUS se configura como um espaço contraditório, marcado simultaneamente por avanços na garantia formal de direitos e por limites em sua concretização. Por isso, evidencia-se a necessidade de novos estudos sobre a implementação das políticas públicas de saúde voltadas à população trans, bem como da atualização dos marcos normativos que regulamentam o Processo Transexualizador, considerando os debates contemporâneos sobre despatologização, autonomia, reconhecimento identitário e cuidado integral. [resumo fornecido pelo autor]
Keywords: Serviço social; Pessoas transgênero; Serviços de saúde para pessoas transgênero; Direito à saúde; Sistema Único de Saúde (Brasil)